(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present study investigates the effectiveness of techno-pedagogy on attitude towards ICT and achievement test in physics among standard IX students. Experimental method is used to select a sample of 64 students from standard IX students. The research tools used was Attitude towards ICT (Constructed by the Investigator) and achievement test in physics. The results of the statistical analyses show a significant correlation of attitude towards ICT and achievement test in physics. A significant difference was found between the independent variable attitude towards ICT and the dependent variable achievement test in physics, which suggests that students with more positive attitude toward ICT had better performance in the achievement test. This implies that these factors play a crucial role in students’ achievement in physics.